A phase 4 study of the safety of the 13-valent pneumococcal conjugate vaccine in children 6 to 17 years of age in India. Issue 37 (31st August 2021) - Chhatwal, Jugesh; Sapru, Amita; Sundaram, Balasubramanian; Shenoy, Bhaskar; Chand, Rohit; Yi, Kevin; Suroju, Suresh; Scott, Daniel A.; Lockhart, Stephen
Highlights: The safety profile of PCV13 was evaluated in Indian subjects aged 6–17 years. PCV13 was well tolerated with an acceptable safety profile. Most safety events were mild to moderate in severity. These data further support PCV13 use in subjects aged 6–17 years in India. Abstract: Purpose: The 13-valent pneumococcal conjugate vaccine (PCV13) was recently approved in India for the prevention of pneumococcal disease in children aged 6 to 17 years based on global data as well as immunogenicity and safety findings from a phase 3 study. The current phase 4 study in India further evaluated the safety profile of PCV13 in this age group to support the positive benefit-risk profile of PCV13. Methods: Healthy male and female children aged 6 to 17 years in India were administered a single intramuscular injection of PCV13. Through 7 days after PCV13 administration, local reactions and systemic events were recorded daily by caregivers in an electronic diary. Adverse events (AEs) were collected from the provision of informed consent through 28–42 days postvaccination. Results: One hundred subjects enrolled in and completed the study. After PCV13 vaccination, 73.9% and 57.8% of subjects reported local reactions and systemic events, respectively. The majority of reactogenicity events were mild to moderate in severity, with injection site pain and fatigue the most frequently reported local reaction and systemic event, respectively. Six subjects reported 7 AEs, all of which were considered unrelated to PCV13. One subject reported a serious AE (acute hepatitis), which was considered unrelated to PCV13 and ultimately resolved. No subjects withdrew because of AEs, and there were no deaths. Conclusion: PCV13 vaccination was well tolerated with an acceptable safety profile in healthy subjects aged 6 to 17 years in India. This work further supports the safety profile of PCV13 for prevention of pneumococcal disease in this age group in India.